Political Trials of the Second Half of the 1930s in the Mirror of the Regional Press - A. I. Lushin (Управленческое консультирование)
The article reveals the reaction of the regional press, and in particular, on the Mordovian regional Committee of the CPSU(b) of the newspaper “Red Mordovia” in the political trials of 1937 in Moscow, and the establishment of Soviet society a climate of suspicion, “hostile environment”, the search for “enemies of the people”, “wreckers”, “spies”, “Trotskyites”, spies of Western and Japanese intelligence agencies.